2020
DOI: 10.3847/1538-4357/ab88a9
|View full text |Cite
|
Sign up to set email alerts
|

Star–Gas Misalignment in Galaxies. I. The Properties of Galaxies from the Horizon-AGN Simulation and Comparisons to SAMI

Abstract: Recent integral field spectroscopy observations have found that about 11% of galaxies show star-gas misalignment. The misalignment possibly results from external effects such as gas accretion, interaction with other objects, and other environmental effects, hence providing clues to these effects. We explore the properties of misaligned galaxies using Horizon-AGN, a large-volume cosmological simulation, and compare the results with those of the Sydney-AAO Multi-object integral field spectrograph (SAMI) Galaxy S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 92 publications
10
26
0
Order By: Relevance
“…We find that ∼ 24% of EAGLE ETGs are misaligned, consistent with the Khim et al (2020b) Horizon-AGN results (23.7±0.2%) but quite different from the SAMI observations (32.7±6.6%). This discrepancy could be explained by the fact that SAMI galaxies are classified as ETGs and LTGs by visual inspection and not through the kinematic thresholds calculated in simulations.…”
Section: Aligned and Misaligned Galaxy Populationssupporting
confidence: 67%
See 1 more Smart Citation
“…We find that ∼ 24% of EAGLE ETGs are misaligned, consistent with the Khim et al (2020b) Horizon-AGN results (23.7±0.2%) but quite different from the SAMI observations (32.7±6.6%). This discrepancy could be explained by the fact that SAMI galaxies are classified as ETGs and LTGs by visual inspection and not through the kinematic thresholds calculated in simulations.…”
Section: Aligned and Misaligned Galaxy Populationssupporting
confidence: 67%
“…They identified the importance of gas loss through black hole feedback and gas stripping during a fly-by passage across a more massive group environment in driving misalignments between stars and SF gas. More recently, Khim et al (2020b) using the Horizon-AGN simulation (Dubois et al 2014) also found that ETGs are substantially more frequently misaligned than LTGs and that misalignment increases with decreasing gas fraction. They compared Horizon-AGN with SAMI, finding a significant discrepancy in the misalignment fraction for galaxies in dense environments.…”
Section: Introductionmentioning
confidence: 97%
“…For this reason, we choose to use only the spin at the central region within r h determined in Section 2.3. We measure the spin vector (S) separately for each particle type (gas, star, and DM) with the same size of aperture, considering the misalignment between them (e.g., Chisari et al 2017;Duckworth et al 2020;Khim et al 2020). The orbital angular momentum vector, L, is calculated by taking the cross product of the position vector (d nei ) and the velocity vector (v nei ) of the nearest neighbor in the reference frame of the target, namely…”
Section: Spin-orbit Anglementioning
confidence: 99%
“…In the previous paper (Khim et al 2020, Paper I), we investigated the properties of misaligned galaxies using the Horizon-AGN simulation and the observational data from SAMI (Bryant et al 2019). We hereby summarize the main results of Paper I.…”
Section: Introductionmentioning
confidence: 97%